Irrationality: a history of the dark side of reason - Smith, Justin E. H. (Princeton University Press, 2020)
Frontmatter -- CONTENTS -- Preface -- Preamble. A Mathematician’s Murder -- Introduction -- CHAPTER ONE. The Self- Devouring Octopus; or, Logic -- CHAPTER TWO. “No-Brainers”; or, Reason in Nature -- CHAPTER THREE. The Sleep of Reason; or, Dreams -- CHAPTER FOUR. Dreams into Things; or, Art -- CHAPTER FIVE. “I believe because it is absurd”; or, Pseudoscience -- CHAPTER SIX. Enlightenment; or, Myth -- CHAPTER SEVEN. The Human Beast; or, the Internet -- CHAPTER EIGHT. Explosions; or, Jokes and Lies -- CHAPTER NINE. The Impossible Syllogism; or, Death -- Conclusion -- Acknowledgments -- Notes -- Bibliography -- Index